Pengujian Pompa Spiral Dengan Kincir Air Pada Aliran Irigasi - Marwanto Marwanto; Asral Asral (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Irrigation water flow can be utilized by installing a tool that is a waterwheel. Now it has been developed in the form of a water wheel pump, where this water pump serves to pump water without using electrical energy but with the help of irrigation flow. The aim of this research was know the characteristics of spiral pump and efficiency of spiral pump with waterwheel. The method used an experimental research that was test directly in the field. The waterwheel used a type of undershot flat blade 2 m diameter with 18 pieces of blade. The flexible hose was 38.1 mm diameter with a total coil of 4.55 windings, and an input diameter of 76.2 mm. The highest flow rate was 0.29 m3/s, the highest spiral pump discharge output was 0.27 l/s with a spiral pump efficiency of 1.54 % and the head was 3.38 m. The lowest flow rate was 0.11 m3/s, the lowest spiral pump discharge output was 0.15 l/s with a spiral pump efficiency of 0.81% and the head was 1.21 m. Therefore, the irrigation flow is influence of the rotation of shaft, the discharge of pump, efficiency and head spiral pump.Keyword: spiral pump, flow rate, head, efficiency.